Bone response to fast-degrading, injectable calcium phosphate cements containing PLGA microparticles - Félix Lanao, Rosa P.; Leeuwenburgh, Sander C.G.; Wolke, Joop G.C.; Jansen, John A. (Biomaterials, 2011)
Apatitic calcium phosphate cements (CPC) are frequently used to fill bone defects due to their favourable clinical handling and excellent bone response, but their lack of degradability inhibits complete bone regeneration. In order to render these injectable CaP cements biodegradable, hollow microspheres made of poly ( d, l-lactic-co-glycolic) acid (PLGA) have been previously used as porogen since these microspheres were shown to be able to induce macroporosity upon degradation as well as to accelerate CPC degradation by release of acid degradation products. Recently, the capacity of PLGA microspheres to form porosity in situ in injectable CPCs was optimized by investigating the influence of PLGA characteristics such as microsphere morphology (dense vs. hollow) and end-group functionalization (acid terminated vs. end-capped) on acid production and corresponding porosity formation in vitro. The current study has investigated the in vivo bone response to CPCs containing two types of microspheres (hollow and dense) made of PLGA with two different end-group functionalizations (end capped and acid terminated). Microspheres were embedded in CPC and injected in the distal femoral condyle of New Zealand White Rabbits for 6 and 12 weeks. Histological results confirmed the excellent biocompatibility and osteoconductivity of all tested materials. Composites containing acid terminated PLGA microspheres displayed considerable porosity and concomitant bone ingrowth after 6 weeks, whereas end capped microspheres only revealed open porosity after 12 weeks of implantation. In addition, it was found that dense PLGA microspheres induced significantly more CPC degradation and bone tissue formation compared to hollow PLGA microspheres. In conclusion, it was shown that PLGA microspheres have a strong capacity to induce fast degradation of injectable CPC and concomitant replacement by bone tissue by controlled release of acid polymeric degradation products without compromising the excellent biocompatibility and osteoconductivity of the CPC matrix.